Global public goods and health: taking the agenda forward - Kaul Inge; Faust Michael (The World Health Organization, 2001)
We examined recent special health initiatives to control HIV/AIDS, malaria, and tuberculosis, and make four policy recommendations for improving the sustainability of such initiatives. First, international cooperation on health should be seen as an issue of global public goods that concerns both poor and rich countries. Second, national health and other sector budgets should be tapped to ensure that global health concerns are fully and reliably funded; industrialized countries should lead the way. Third, a global research council should be established to foster more efficient health-related knowledge management. Fourth, managers for specific disease issues should be appointed, to facilitate policy partnerships. Policy changes in these areas have already begun and can provide a basis for further reform.